2019
DOI: 10.1541/ieejpes.139.106
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Operation of Battery Energy Storage System and Thermal Generators for Supply-Demand Balance Maintenance and Efficient Use of Photovoltaic Energy

Abstract: In future power systems with extremely large integration of photovoltaic (PV) generation, it is necessary to not only properly maintain supply-demand balance without power shortfall but also utilize as much PV energy as possible. The application of PV power forecast and energy storage devices to power system operation is necessary.In this study, we propose a method for determining and modifying the charging and discharging schedule of a battery energy storage system (BESS) and the unit commitment of thermal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, metaheuristic methods were applied to supply‐demand scheduling in power systems with renewable energies 8,9 . Our research group has studied PV supply‐demand scheduling and operation methods using BESS as well as PV forecasting based on deterministic approach 5,6,10 . Particularly, we proposed a method of coordinated operation of thermal generators and BESS, and showed that supply‐demand imbalance can be mitigated when UC and BESS charge‐discharge schedule are updated based on PV output values predicted every 6 h 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, metaheuristic methods were applied to supply‐demand scheduling in power systems with renewable energies 8,9 . Our research group has studied PV supply‐demand scheduling and operation methods using BESS as well as PV forecasting based on deterministic approach 5,6,10 . Particularly, we proposed a method of coordinated operation of thermal generators and BESS, and showed that supply‐demand imbalance can be mitigated when UC and BESS charge‐discharge schedule are updated based on PV output values predicted every 6 h 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In that method, supply‐demand scheduling and operation are formulated in terms of a MILP (Mixed Integer Linear Programming) problem; in so doing, schedules are updated and operating points are determined every half hour using actual PV output data and a latest PV forecast dataset (generation frequency: 3 h). In addition, detailed operating conditions ignored in Reference 10 are taken into account: output ramp rate, continuous up/down time, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, voltage management and protection coordination become more difficult. To solve these problems, battery energy storage systems (BESSs) have been explored as a means to maintain supply‐demand balance in bulk power systems 4,5 and to regulate voltage in distribution networks 6 . Under the feed‐in tariff system (FIT) launched in 2012, PV was purchased at a fixed price, but when FIT time limit will expire for increasing PV output, one can expect for higher PV energy transaction activity in the electricity market 7 .…”
Section: Introductionmentioning
confidence: 99%